Preliminary Psychometric Evaluation of the Arabic Trichotillomania Dimensional Scale (TTM‐D) in an Online Convenience Sample From Five Arab Countries - Anthony Rizk; Adella Ibrahim; Diana Malaeb; Amira M. Ali; Mirna Fawaz; Nouran Omar El Said; Nisma Merdad; Rizwana Amin; Wizra Saeed; Muna Barakat; Rami Mosleh; Rita Doumit; et al. (Health Science Reports, 2026)
ABSTRACT Background Trichotillomania (TTM) is a disorder within Obsessive–Compulsive and Related Disorders, involving repetitive hair‐pulling leading to hair loss and functional impairment. It remains under‐investigated in the Middle East. The Trichotillomania Dimensional Scale (TTM‐D) has not been validated in Arabic‐speaking populations. Methods Arabic‐speaking participants from Saudi Arabia, Egypt, Lebanon, Palestine, and Jordan were recruited online via snowball sampling (December 2024 and January 2025). The TTM‐D was translated using forward‐backward translation and expert panel review. Results A total of 1494 participants from five Arab countries completed the survey. The structure of the TTM‐D showed mixed model fit (CFI = 0.957, TLI = 0.914, RMSEA = 0.139, SRMR = 0.044), with excellent internal consistency ( α = 0.95, ω = 0.95) and satisfactory convergent validity (AVE = 0.55). Measurement invariance across gender (biological sex) was supported with no significant differences. Concurrent validity was demonstrated through significant correlations with depression‐anxiety ( r = 0.29), shame ( r = 0.28–0.30), stress ( r = 0.13), and loneliness ( r = 0.27). Conclusion The Arabic TTM‐D demonstrated strong psychometric properties. These results support it as a culturally sensitive and reliable tool for assessing TTM in Arab populations. Further validation is needed to enhance its diagnostic utility and establish clinical cut‐off scores.